2021
DOI: 10.2147/opth.s316697
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Intraocular Lens Power Calculation Formulae in Children

Abstract: Purpose To compare the accuracy of IOL power calculation formulae in a large cohort of children who underwent IOL implantation. Setting Cairo University Children Hospital. Design Retrospective, case series. Methods A retrospective chart review of all children <14 years, who underwent primary or secondary IOL implantation in Cairo University Children Hospital from January 2016 to December 2019, was performed. Absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
1
2
Order By: Relevance
“…Others report lower predictability using the SRK/T formula as well, with a higher myopic shift, especially in young children, or short and normal eyes and lower amount of eyes within ±0.5 D from target refraction. [16][17][18][19][20][21][22] Others report a hyperopic shift for all of their tested formulas using second and third generation formulas, which is contrary to our results. 22 In previous studies, it was shown that in pediatric cataract surgery, the implantation of an IOL with posterior optic capture is the best alternative to prevent posterior capsule opacification.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Others report lower predictability using the SRK/T formula as well, with a higher myopic shift, especially in young children, or short and normal eyes and lower amount of eyes within ±0.5 D from target refraction. [16][17][18][19][20][21][22] Others report a hyperopic shift for all of their tested formulas using second and third generation formulas, which is contrary to our results. 22 In previous studies, it was shown that in pediatric cataract surgery, the implantation of an IOL with posterior optic capture is the best alternative to prevent posterior capsule opacification.…”
Section: Discussioncontrasting
confidence: 99%
“…Others report lower predictability using the SRK/T formula as well, with a higher myopic shift, especially in young children, or short and normal eyes and lower amount of eyes within ±0.5 D from target refraction. 16–22 Others report a hyperopic shift for all of their tested formulas using second and third generation formulas, which is contrary to our results. 22…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent study, a significant negative correlation between the age of the patient and predictive error of the SRK/T formula was found. [ 37 ] Overall, all IOL power calculation formulae tend to be variable in children, especially in children <2 years, with AL <19 mm and K readings >46.5 D.[ 36 ] In addition, age at the time of surgery significantly contributes to the refractive surprise using all formulas. [ 38 ] SRK/T and Holladay I formulas give better results in children aged less than 2 years.…”
Section: Age and Iol Power Calculation Formulamentioning
confidence: 99%